2020
DOI: 10.3233/blc-200318
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Novel Urine-Based mRNA Tests (Xpert and Urinary Metabolomics Markers Assay) for Bladder Cancer Detection in Patients with Hematuria

Abstract: BACKGROUND: Hematuria is the most frequent presenting symptom in the vast majority of bladder cancer (BC) patients. The current recommended evaluation of hematuria includes cross sectional imaging and cystoscopy with possible high negative results, expensive costs and substantial patient burden. OBJECTIVES: To validate novel urine-based mRNA-dependant tests; Xpert test and urinary metabolomics assay (CRAT and SLC 25A20genes expression) for BC detection in patients with hematuria. METHODS: Patients presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Therefore, we could not use a fixed RNA amount, but have decided to use an equal original urine volume for input normalization n amplification reactions. Such decision is in line with the common practice in diagnostic sampling 22 . MiRNAs are among the exosome cargo molecules that have elicited substantial interest and have been early approached for potential clinical interest.…”
Section: Resultssupporting
confidence: 71%
“…Therefore, we could not use a fixed RNA amount, but have decided to use an equal original urine volume for input normalization n amplification reactions. Such decision is in line with the common practice in diagnostic sampling 22 . MiRNAs are among the exosome cargo molecules that have elicited substantial interest and have been early approached for potential clinical interest.…”
Section: Resultssupporting
confidence: 71%
“…The combination of 3 miRNAs and 2 lncRNAs, overly altered in BCa, was also evaluated, but did not display optimal diagnostic features (AUC = 0.910; sensitivity = 87.2% and specificity = 83.3%) [ 145 ], the same as coupling metabolomics assay and 5 target mRNAs (Xpert panel) resulting in NPV of 98.2%, not much better than when used singularly [ 146 ].…”
Section: Resultsmentioning
confidence: 99%
“…An overview of the five studies is shown in Table 2. The Xpert Bladder Cancer test, which assessed five mRNA targets ( ABL1, CRH, IGF2, UPK1B, and ANXA10 ) was evaluated in two studies [18 ▪ ,19]. This test combines expression levels of the markers in a linear discriminate analysis (LDA) to classify samples as positive or negative in a linear model [23].…”
Section: Resultsmentioning
confidence: 99%
“…Five articles reported on the diagnostic performance of an RNA-based urinary assay as a diagnostic tool to detect urothelial cancer of the bladder in patients presenting with hematuria [18 ▪ ,19–22]. In all studies, the presence of urothelial cancer was confirmed by histological examination.…”
Section: Resultsmentioning
confidence: 99%